Medical-Adapted Fable in Teaching English for Nursing Purposes - Ferra Dian Andanty; Rahmat Setiawan (English Language in Focus (ELIF), 2025)
English proficiency is essential in nursing education, as nurses must communicate medical information accurately while demonstrating empathy and ethical awareness. However, many English for Specific Purposes (ESP) courses remain limited to vocabulary and grammar memorization, neglecting contextual and humanistic aspects of learning. This study introduces medical-adapted fables as an alternative medium for English instruction in nursing. Employing a mixed-method exploratory–descriptive design, data were gathered from 150 nursing students in Surabaya through questionnaires, complemented by interviews with three participants for deeper insights. Findings reveal that students could recognize key medical vocabulary such as blood pressure (80%), infection (76.7%), and diagnosis (74.7%), along with medical devices including thermometer (86.7%), stethoscope (83.3%), and syringe (80.7%). Ethical communication values were also strongly perceived, particularly empathy (88%), active listening (84.7%), and confidentiality (76.7%). Perception scores exceeded 4.2 on a Likert scale, indicating positive responses toward storytelling as a learning tool. Interviews further highlighted that fables provided memorable and emotionally engaging contexts, fostering confidence and sensitivity in English use. The novelty of this research lies in integrating narrative pedagogy into ESP for nursing, offering promising implications for vocabulary learning, ethical awareness, and global communication readiness.